(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
This article explores the optimization of treatment approaches for chronic allergic dermatoses using traditional medicine methods. Chronic allergic dermatoses refer to long-lasting skin conditions characterized by inflammation, itching, and immune system dysregulation due to allergic reactions. Traditional medicine systems, such as Traditional Chinese Medicine and Ayurveda, offer a range of modalities and strategies to address these conditions. This article discusses various traditional medicine approaches, including acupuncture, herbal formulations, dietary recommendations, external therapies, energy practices, and lifestyle modifications. It also emphasizes the importance of personalized treatment plans, follow-up, and collaboration between traditional medicine practitioners and conventional healthcare professionals. While scientific evidence regarding the efficacy of traditional medicine methods may vary, continued research and integration of traditional and conventional approaches can contribute to a comprehensive understanding and optimization of treatment for chronic allergic dermatoses.